Kepemilikan Satuan Rumah Susun Bagi Warga Negara Asing Di Indonesia - Anak Agung Ngurah Sentana Putra; I Nyoman Putu Budiartha; Ni Made Puspa Sutariujianti (Warmadewa Press, 2022)
The Indonesian Flats Ordinance is regulated by the Ministerial Ordinance or the head of the agency that handles affairs in the agricultural sector and aims to create legal certainty and protection for the owner of the right or house. The purpose of this research is to discuss the regulation of foreign houses in Indonesia and to find out what the meaning of foreign house law is in Indonesia. The sources of legal materials for this research are primary and secondary legal materials, where primary legal materials come from legislation relevant to the case raised. Meanwhile, secondary legal materials come from legal books and journals that can support primary sources. The collection of primary and secondary legal materials is carried out by collecting, reading and recording legal materials. However, first an agreement must be reached between the owners of the land rights, then the rights are submitted to the State Land Agency (BPN) under the attorney's power to sell the alternative, and so on. The process of transferring the right to housing into the use rights of foreigners. In addition, the legal impact of foreign housing ownership in Indonesia based on Government Regulation of the Republic of Indonesia Number 103 of 2015 aims to provide legal certainty regarding permits for foreign citizens. (Foreigners) own a flat (salsun)/apartment built on a plot of land that has the right to be used.